Origin and post-harvest losses of vegetables in the microregion of Chapadinha, Maranhão, Brazil - Tiago Fernando Riew Tomm; Edmilson Igor Bernardo Almeida; Kessia Tenório Figueirinha; Lusiane de Sousa Ferreira; Márcia Maria de Souza Gondim; Deucleiton Jardim Amorim (Agro@mbiente On-line)
Research involving estimation of post-harvest losses of vegetables is limited in the state of Maranhão (MA), however, they are essential to identify of causes of losses, as well as for reducing them. The objective of the current study was to describe the cultivation and post-harvest losses of vegetables in the municipalities of Anapuru, Belágua, Chapadinha, Mata Roma, São Benedito and Urbano Santos, state of Maranhão, northern Brazil. The information was obtained by questionnaires given to the traders from the main vegetable trading centres for each municipality. The questions covered the socioeconomic aspects of handling, transportation, storage and commercialization of vegetables. While many traders had a full secondary education (37%), they have little technical knowledge of production, management (83%) and marketing (82%) of vegetables. Cultivation is carried out mainly in greenhouses (77%), with many vegetables coming from other states (89%), such as Ceará, via asphalted roads (100%). Physiological disorders, such as rapid maturation, wilting and budding, were the main causes of loss. Rank losses, in order of decreasing losses were: tomato (18.38 ± 0.39%) > potato (13.82 ± 0.11%) > bell pepper (10.13 ± 0.07%) > carrot (9.35 ± 0), 09%) > onion (7.31 ± 0.15%) > lettuce (6.16 ± 0.15%). The losses were significant and there is a clear need for training on good post-harvest practices, effective management of the quantity offered, and government incentives to expand the olericulture in the Chapadinha microregion.